ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, AND CAPITAL) PADA PT. BANK MANDIRI PERSERO TBK TAHUN 2013-2022 - Indah Tadarus, Fitria; Gunawan, Hendri (Journal of Research and Publication Innovation, 2024)
This study aims to analyze the financial performance of PT. Bank Mandiri (Persero) Tbk which includes aspects of Risk Profile, Good Corporate Governance (GCG), Earnings and Capital as a whole. The type of research used by the author is quantitative descriptive research. The population in this study is PT. Bank Mandiri (Persero) Tbk for the period 2013-2022 and the sample in this study is the financial statements for the period 2013-2022 at PT. Bank Mandiri (Persero) Tbk. The variables in this research are financial performance and RGEC ratio. The type of data used by researchers is secondary data. The data collection technique used by this researcher is documentation in the form of financial reports. The results of the financial performance assessment using the RGEC ratio show that the health level of PT. Bank Mandiri (Persero) Tbk in 2013-2022 based on the Very Healthy RGEC method. The Risk Profile factor is measured by the NPL ratio with an average value of 2.74% and LDR with an average value of 93.8% which shows that risk management has been implemented fairly soundly. The Good Corporate Governance factor shows that PT. Bank Mandiri (Persero) Tbk has implemented good corporate governance with a Composite Rating of 2. The Earnings Factor as measured by ROA with an average value of 2.57% shows very healthy results. The Capital Factor as measured by the CAR ratio with an average value of 19.5% shows very healthy results.